Practice beats age: co-activation shapes heritage speakers’ lexical access more than age of onset - Sagarra, Nuria; Casillas, Joseph V. (Frontiers in Psychology, 2023)
Probabilistic associations make language processing efficient and are honed through experience. However, it is unclear what language experience factors explain the non-monolingual processing behaviors typical of L2 learners and heritage speakers (HSs). We investigated whether AoO, language proficiency, and language use affect the recognition of Spanish stress-tense suffix associations involving a stressed syllable that cues a present suffix (SALta ‘s/he jumps’) and an unstressed syllable that cues a past suffix (SALtó ‘s/he jumped’). Adult Spanish-English HSs, English-Spanish L2 learners, and Spanish monolinguals saw a paroxytone verb (stressed initial syllable) and an oxytone verb (unstressed initial syllable), listened to a sentence containing one of the verbs, and chose the one they heard. Spanish proficiency measured grammatical and lexical knowledge, and Spanish use assessed percentage of current usage. Both bilingual groups were comparable in Spanish proficiency and use. Eye-tracking data showed that all groups fixated on target verbs above chance before hearing the syllable containing the suffix, except the HSs in the oxytones. Monolinguals fixated on targets more and earlier, although at a slower rate, than HSs and L2 learners; in turn, HSs fixated on targets more and earlier than L2 learners, except in oxytones. Higher proficiency increased target fixations in HSs (oxytones) and L2 learners (paroxytones), but greater use only increased target fixations in HSs (oxytones). Taken together, our data show, that HSs’ lexical access depends more on number of lexical competitors (co-activation of two L1 lexica) and type (phonotactic) frequency than token (lexical) frequency or AoO. We discuss the contribution of these findings to models in phonology, lexical access, language processing, language prediction, and human cognition.